Symmetric Spaces and Fixed Points of Generalized Contractions - Sarah Alshehri; Ivan Aranđelović; Naseer Shahzad (Abstract and Applied Analysis)
Some fixed point results in semi-metric spaces as well as in symmetric spaces are proved. Applications of our results to probabilistic spaces are also presented.